2016
DOI: 10.1021/acscentsci.6b00168
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion-Controlled Rotation of Triptycene in a Metal–Organic Framework (MOF) Sheds Light on the Viscosity of MOF-Confined Solvent

Abstract: Artificial molecular machines are expected to operate under conditions of very low Reynolds numbers with inertial forces orders of magnitude smaller than viscous forces. While these conditions are relatively well understood in bulk fluids, opportunities to assess the role of viscous forces in confined crystalline media are rare. Here we report one such example of diffusion-controlled rotation in crystals and its application as a probe for viscosity of MOF-confined solvent. We describe the preparation and chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
73
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(76 citation statements)
references
References 54 publications
2
73
0
1
Order By: Relevance
“…MOFs can be utilized in the pursuit of potential artificial molecular machines. A set of pillared paddlewheel MOFs were prepared containing 9,10‐bis(4‐pyridylethynyl)triptycene with the purpose to act simultaneously as a pillar and molecular rotator 268 , three axially substituted dicarboxylate linkers of varying lengths and steric bulk were also employed (Figure ) . Changing the linker from benzene to a biphenyl and then a triptycene moiety, 268 a , 268 b , and 268 c , showed 2‐fold, 4‐fold, and no catenation, respectively, when crystalized from DMF, in correlation to the amount of space available in their 2D frames.…”
Section: Applications Of Rigid‐linear Linkers In Molecular Rods and Rmentioning
confidence: 99%
See 1 more Smart Citation
“…MOFs can be utilized in the pursuit of potential artificial molecular machines. A set of pillared paddlewheel MOFs were prepared containing 9,10‐bis(4‐pyridylethynyl)triptycene with the purpose to act simultaneously as a pillar and molecular rotator 268 , three axially substituted dicarboxylate linkers of varying lengths and steric bulk were also employed (Figure ) . Changing the linker from benzene to a biphenyl and then a triptycene moiety, 268 a , 268 b , and 268 c , showed 2‐fold, 4‐fold, and no catenation, respectively, when crystalized from DMF, in correlation to the amount of space available in their 2D frames.…”
Section: Applications Of Rigid‐linear Linkers In Molecular Rods and Rmentioning
confidence: 99%
“…As et of pillared paddlewheel MOFs were prepared containing 9,10-bis(4-pyridylethynyl)triptycene with the purpose to act simultaneously as ap illar and molecular rotator 268,t hree axially substituted dicarboxylatel inkers of varying lengths and steric bulk werea lso employed ( Figure 50). [328] Changing the linker from benzene to ab iphenyl and then at riptycene moiety, 268 a, 268 b,a nd 268 c,s howed 2-fold, 4-fold, and no catenation, respectively,w hen crystalized from DMF,i nc orrelation to the amounto fs pace available in their 2D frames. Tight packing is observed for the two catenated structures while the triptycene derivative shows no contacts between pillars and linkers in the lattice.R otation is occurring in this compound via aB rownian three-fold jumping mechanism and, as there are no sterici nteractions in this molecule, it is suggested that the confined DMF molecules in the lattice cause the rotation.…”
Section: Metalorganic Framework (Mofs)mentioning
confidence: 99%
“…The three‐dimensional rigid triptycene frameworks have been used as building blocks towards stable 3D or 2D microporous polymers with high surface areas . Triptycenes have also been successfully utilized in Metal Organic Framework (MOF) chemistry, where, for example, diffusion‐controlled rotation of triptycene was investigated in order to measure the viscosity of MOF‐confined solvents …”
Section: Introductionmentioning
confidence: 99%
“…[8] Triptycenes have also been successfully utilized in Metal Organic Framework (MOF) chemistry, [9,10] where, for example, diffusion-controlled rotation of triptycene was investigated in order to measure the viscosity of MOFconfined solvents. [11] The features of the functional triptycene-derived materials are mainly determined by the properties of the triptycene subunits concerned. These properties, in turn, depend on the functional groups mounted on the bare triptycene framework, and interactions between them.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] To date, examples have been reported of amphidynamic crystals with the potential of controlling gas adsorption and desorption, [12,15] electric, [25][26][27][28]33] optic, [29,30] shape memory, [31][32][33] and luminescence, [35][36][37][38] among other properties. [9][10][11][12]34] One of the most robust molecular architectures for the formation of amphidynamic crystals is based on the use of dumbbell shaped molecular rotors. [9,10,12] Their structures are generally based on ac entral phenylene rotator linked by ad ialkyne axle to bulky groups that build up the lattice and play the role of as tator.A mphidynamic crystals possess ar elatively low packing density and/or ar elatively fluid region near the rotator, which makes it possible for fast molecular rotation to occur in the solid state.W ith that in mind we recently designed an amphidynamic crystal with rotationally controlled phosphorescence by incorporating ag old(I) complex within the dumbbell shaped motif in complex 1 (Figure 1a).…”
mentioning
confidence: 99%